2022
DOI: 10.3390/ijms23168890
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of High-Fat Diet Exposure on Oocyte and Follicular Quality: A Molecular Point of View

Abstract: Worldwide, infertility affects between 10 and 15% of reproductive-aged couples. Female infertility represents an increasing health issue, principally in developing countries, as the current inclinations of delaying pregnancy beyond 35 years of age significantly decrease fertility rates. Female infertility, commonly imputable to ovulation disorders, can be influenced by several factors, including congenital malformations, hormonal dysfunction, and individual lifestyle choices, such as smoking cigarettes, stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 58 publications
(77 reference statements)
3
16
0
Order By: Relevance
“…The current results showed that hyperlipidemia and fatty liver changes are also linked to severe impairments in the reproductive organs ( Figure 7 , Figure 8 and Figure 9 ). HCD supplementation caused a decrease in the mature vitellogenic stage of approximately 2.7%, while the ND group showed 6.5%, indicating that elevated oxidative stress caused by hyperlipidemia inhibited oocyte maturation, as reported elsewhere [ 43 , 44 ]. In the current study, however, the co-supplementation of Cuban policosanol resulted in the largest increase in early-vitellogenic and mature-vitellogenic oocytes, indicating enhanced oocyte maturation and folliculogenesis.…”
Section: Discussionsupporting
confidence: 78%
“…The current results showed that hyperlipidemia and fatty liver changes are also linked to severe impairments in the reproductive organs ( Figure 7 , Figure 8 and Figure 9 ). HCD supplementation caused a decrease in the mature vitellogenic stage of approximately 2.7%, while the ND group showed 6.5%, indicating that elevated oxidative stress caused by hyperlipidemia inhibited oocyte maturation, as reported elsewhere [ 43 , 44 ]. In the current study, however, the co-supplementation of Cuban policosanol resulted in the largest increase in early-vitellogenic and mature-vitellogenic oocytes, indicating enhanced oocyte maturation and folliculogenesis.…”
Section: Discussionsupporting
confidence: 78%
“…In this context, diet, including hypercaloric nutrition, may result in metabolic derangements and in body weight increase which promote obesity, an increase in ovarian dysfunction, and the risk of infertility. Indeed, obesity perturbates the hypothalamic–pituitary–ovarian axis dialogue through an inhibitory action exerted by the adipose tissue that has a recognized critical role in maintaining the endocrine/paracrine control of the gonads, with the aim of synchronously regulating the follicle–oocyte development over time until ovulation [ 2 , 3 ]. To date, many research studies that have clarified the mechanisms behind high-fat-related infertility in mammals were carried out in experimental animal models [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pro-inflammatory mediators may inhibit insulin receptors, reduce insulin sensitivity and aggravate IR, consequently worsening reproductive dysfunction ( 41 , 42 ). Obesity can induce higher levels of inflammatory mediators in the ovary, which may cause irreversible damage to the oogenesis and ovary function ( 21 , 43 ). Oxidative stress, closely related to inflammatory response, can also lead to oocyte apoptosis and ovarian dysfunction ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, closely related to inflammatory response, can also lead to oocyte apoptosis and ovarian dysfunction ( 44 ). The change in obesity-induced inflammation and oxidative stress pathways may alter the expression of genes related to oocyte quality, thus adversely affecting the subsequent embryogenesis ( 21 ). Furthermore, the NLRP3 inflammasome and the chemokine decoy receptor D6, two representative uterine inflammatory mediators, may disturb the maternal–fetal interface with the subsequent occurrence and progress of obstetric complications ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation